Investigating patterns of language dominance and mixed dominance among Farsi-German bilingual children in Germany - Ghaemi, Tina; Thillmann, Jenny; Scherger, Anna-Lena (Frontiers in Language Sciences, 2025)
IntroductionThis study aimed to operationalize language dominance based on relative language proficiency across vocabulary and morphosyntax and to classify children into dominant and balanced groups. These language dominance classifications were compared with those based on relative language experience, which is characterized by two child-external factors: relative language exposure and use in Farsi. This study further explored child-internal and -external factors contributing to mixed language dominance, defined as a divergence in dominance classification across linguistic domains.MethodsThirty-two Farsi-German bilingual children (age range: 3.10–8.9 years, mean = 6.9 years, SD = 16.8), who speak Farsi as their heritage language (HL) in Germany, participated in the study. All children were tested on vocabulary and morphosyntax in both Farsi and German using the LITMUS-Crosslinguistic Lexical Tasks (CLTs) and Sentence Repetition Tasks (SRTs). Children's relative language experience was documented based on parental ratings.ResultsThe findings indicated that the 0.5 SD-based classification is a reliable method for identifying language dominance. In contrast, relative language experience in the HL only partially predicted Farsi-dominant status when compared to German-dominant and balanced children across domains. Mixed dominance was observed in 45% of the children and was influenced by relative language use in the HL and length of exposure (LoE) to German.DiscussionOverall, this study highlighted that using a 0.5 SD threshold provides a more consistent approach to determining relative language proficiency and that mixed dominance is a characteristic feature of bilingualism. Recognizing this feature and its contributing factors may help reduce the risk of misdiagnosing developmental language disorder (DLD) in bilingual children.